Process Management Practice Analysis on Organizational Performance Mediated by Knowledge Creation - Wartini, Sri; Wiradendi, Cristian; Imaniyati, Nani; Hadijah, Hadi Siti (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2023)
Knowledge is an important resource that supports process management to produce efficient and effective products and services. The research objective is to examine the influence of process management on performance through the role of knowledge creation in the future of new normal. Survey method with saturated sample was used for data collection on 126 head of study programs at public and private universities in the city of Semarang. Partial Least Square-Structural Equation Modeling (PLS-SEM) approach was used to analyze the data. The results of the study found that process management has no direct effect on organizational performance and knowledge creation directly affects performance. Tests indirectly show that the knowledge creation shown to mediate the effect of process management on organizational performance. Implications of research for leaders as a consideration in the implementation of process management practices and knowledge creation in the new normal era of the organization. Suggestions for future research should use a longitudinal design, so that studies can be developed and explored more deeply and prepare other techniques or strategies as alternative solutions in data collection so that they are in accordance with the set targets